2021
DOI: 10.21182/jmisst.2021.00122
|View full text |Cite
|
Sign up to set email alerts
|

Full Endoscopic Transforaminal Lumbar Discectomy: A Literature Review

Abstract: Since its introduction in 1973, Kambin's triangle had made endoscopic transforaminal lumbar discectomy (TELD) possible. Dr. Yeung further developed a complete spinal endoscope system and approach methods (the Yeung endoscopic spine system). With the advancement of endoscopic instruments such as the high-speed burr, reamer, and trephine, Dr. Hoogland introduced foraminoplasty methods to extract herniated disks. Since then, the surgical field of TELD has been broadly widened. Many interesting and innovative surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The present experience shows a low incidence of recurrent relapsed disc following the endoscopy procedure. This incident is low, if compared to the data from recently published meta-analyses [13][14][15][16][17][18][19]. In our opinion, this is not surprising since we choose performing endoscopic removal only in laterally located herniated discs, and we strongly recommend this policy in the patients' selection for endoscopic lumbar surgery.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The present experience shows a low incidence of recurrent relapsed disc following the endoscopy procedure. This incident is low, if compared to the data from recently published meta-analyses [13][14][15][16][17][18][19]. In our opinion, this is not surprising since we choose performing endoscopic removal only in laterally located herniated discs, and we strongly recommend this policy in the patients' selection for endoscopic lumbar surgery.…”
Section: Discussionmentioning
confidence: 73%
“…Several papers have been recently published in regard to the use, the techniques, and the results of endoscopic lumbar disc surgery. A comprehensive meta-analysis has appeared recently in a highly ranked international journal devoted to spinal surgery [13][14][15][16][17][18][19]. These analyses reported the results of spinal endoscopic vs. open surgery in an extensive number of well documented cases, and concluded that endoscopy and microdiscectomy would bring the same results in operated HLDs.…”
Section: Introductionmentioning
confidence: 99%